The Isolation and Identification of Salmosamonella typhi from clinical samples with molecular detection of O-antigen encoded genes - jassim, Huda (Iraqi Journal of Pharmaceutical Sciences, 2023)
Abstract Antibiotic treatment of S.typhi is difficult as compared to treatment of acute infection. Antibiotic resistance carried against S.typhi by using 6 kinds of antibiotics from different classes, their results showed that all isolates were high resistance to Ampicillin (99%), Gentamicin (98%), Amikacin (79%) and less resistances Trimethoprim (55%) , Imipenem (60%) and Ceftriaxone(66%) . The present study focused on the molecular detection of Wzx flippase, Wzy polymerase genes in some Salmonella typhi isolates, Samples were collected from typhoid patients by classical lab work. Antibiotics susceptibility were investigated using disc diffusion method. The DNA and molecular Wzx flippase, Wzy polymerase were implemented using specific primers. The results showed that there was 33.33% having Wzy gene. The Wzx gene didn’t observed in any Salmonella isolates. The present study concluded that there was an important of the genetic diversity of O-antigen encoded genes included Wzx and Wzy which may be effect in typhoid diagnosis and treatment types.